L’Alaska Railroad Corporation : un modèle ferroviaire original aux confins des États-Unis entre diversification commerciale et stratégie touristique intégrée - Matthieu Schorung (EchoGéo)
The Alaska Railroad Corporation – ARRC – is a unique railway model in the United States: a public company owned by the State of Alaska, the not-divided freight and passenger services, a multifaceted financial strategy. This rail line has enabled the settlement and the exploitation of Alaska. This transportation mode is nowadays a key actor in the Alaskan transport system. Moreover, its tourism strategy makes the ARRC a leading player in the development of tourism and the enhancement of Alaska. This article aims to analyze the main characteristics of the company and the components of its success and to count the ARRC strategy as a structuring factor of the current economic and territorial dynamics in Alaska.